Impact of Sampling Time Variability on Tacrolimus Dosage Regimen in Pediatric Primary Nephrotic Syndrome: Single-Center, Prospective, Observational Study - Huang, Lingfei; Wang, Junyan; Yang, Jufei; Zhang, Huifen; Hu, Yan; Miao, Jing; Mao, Jianhua; Fang, Luo (Frontiers in Pharmacology, 2022)
Background：Tacrolimus (TAC) is an important immunosuppressant for children with primary nephrotic syndrome (PNS). The relationship between sampling time variability in TAC therapeutic drug monitoring and dosage regimen in such children is unknown. Methods: In this single-center, prospective, observational study, we evaluated the sampling time variability, concentration error (CE), relative CE (RCE) and the impact of the sampling time on TAC dosage regimens in 112 children with PNS and 188 TAC samples. Nominal concentration (Cnom) at 12-hour after last TAC dose was simulated based on observed concentration (Cobs) via previously published pharmacokinetic models, then CE and RCE were calculated. Inappropriate dosing adjustments resulting from deviated sampling time were evaluated based on a target Cnom of 5–10 ng/mL. Results: We found that 32% and 68% of samples were respectively collected early (2–180 min) and delayed (4–315 min). Furthermore, 24%, 22%, 22%, and 32% of blood samples were drawn within deviations of ≤ 0.5, 0.5–1, 1–2, and > 2 h, respectively, and 0.3 ng/mL of CE and 6% RCE per hour of deviation occurred. Within a deviation of >2 h, 25% of Cobs might result in inappropriate dosing adjustments. Early and delayed sampling might result in inappropriate dose holding or unnecessary dose increments, respectively, in patients with Cobs ~ 5 ng/mL. Conclusions: Variable sampling time might lead to inappropriate dosing adjustment in a minority of children with PNS, particularly those with TAC Cobs ~ 5 ng/mL collected with a deviation of > 2 h.